Devising an approach for the automated restoration of shipmaster’s navigational qualification parameters under risk conditions - Ponomaryova, Victoria; Nosov, Pavlo; Ben, Andrii; Popovych, Ihor; Prokopchuk, Yurii; Mamenko, Pavlo; Dudchenko, Sergiy; Appazov, Eduard; Sokol, Ihor (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the safety control system of ship management, by identifying and restoring the qualification parameters of shipmasters in critical situations. The task solved in the study is the timely determination of an insufficient level of qualification for the performance of certain operations in controlling the movement of the ship, by applying a formal-logical model of detecting the intuitive actions of the operator-shipmaster and gradually restoring his/her qualification parameters using the devised method. The stages of development and the formal-logical structure of the model and method in terms of cognitive automation were described in detail as the study results. It was possible to ensure early detection of risks when controlling the movement of the ship in 56 % of cases, during a laboratory experiment on simulators, which in 24 % of cases turned out to be particularly dangerous. The interpretation of the results involved algorithmizing complex and formalized data on the actions of operators and the application of the method of restoring their qualification parameters, which allowed a comprehensive approach to safety management. The distinguishing features of the findings were to predict the level of danger by simulating maritime operations with input navigational and individual conditions. This made it possible to improve the effectiveness of operations to 89 %, reduce the phenomenon of loss of control over the course to 32 %, reduce critical situations to 7 % and the cost of resources. The scope and conditions of practical use involve a comprehensive assessment of external and internal influences on the level of danger, delay in decision-making by operators, as well as sailing conditions. The simulation results could be used to devise strategies for planning maneuvers, predicting risks, and developing maritime security systems